Post-transplant lymphoproliferative disorder of the pediatric airway: Presentation and management. (July 2016) - O'Neill, Allison F.; Adil, Eelam A.; Irace, Alexandria L.; Neff, Laura; Davis, Ian J.; Perez-Atayde, Antonio R.; Voss, Stephan D.; Weinberg, Olga; Rahbar, Reza
Abstract: Objective: Post-transplant lymphoproliferative disorder (PTLD) is a rare complication of immunosuppression with little consensus on its evaluation and management. The purpose of this contemporary review is to describe a pediatric patient with PTLD of the airway and review the literature to provide multidisciplinary recommendations regarding management. Data Sources: Retrospective chart and literature review. Review Methods: A pediatric patient with PTLD of the airway is described. An extensive literature search to review the existing data on pediatric PTLD of the upper airway was also performed. Results: A pediatric patient with mixed fetal/embryonal hepatoblastoma developed laryngo-tracheal PTLD following liver transplantation. Diagnostic positron emission tomography (PET) scan demonstrated multiple sites of abnormal fluorodeoxyglucose (FDG) uptake within the larynx, distal esophagus, cervical lymph nodes, and abdomen concerning for PTLD. Laryngeal biopsy demonstrated Epstein–Barr virus (EBV) positive cells confirming the diagnosis. Rituximab therapy and reduction of immunosuppression resulted in resolution of his laryngeal disease in 3 months. An extensive literature search to review the existing data on pediatric PTLD of the larynx and trachea revealed 14 reported cases. Conclusions: PTLD of the pediatric airway is an EBV-associated disease that requires a high index of suspicion as patients can often present with non-specific signs and symptoms but progress to have significant airway compromise. Evaluation consists of peripheral blood polymerase chain reaction (PCR) assays, biopsy, and PET/CT imaging. Management options include reduction of immunosuppression and/or systemic therapies.